Developing a religiosity scale for Indonesian Muslim youth - Abdullah, Shodiq; Warsiyah, Warsiyah; Ju'subaidi, Ju'subaidi (REID (Research and Evaluation in Education), 2023)
This study aims to construct and test the validity of the Islamic youth religiosity scale. The population in this study is Muslim students of senior high schools in Surakarta, Central Java, with a sample of 258 established using the random sampling technique. The data analysis used the Linear Structural Model. The result shows that the RMSEA (â‰¤ 0.08) and GFI (â‰¥ 0.09) values from the four dimensions (belief, ritual, social, commitment meet the standard values of compatibility with the respective values for RMSEA beliefs = 0.055 GFI = 0.94, RMSEA rituals = 0.026 GFI = 0.99, social RMSEA = 0.059 GFI = 0.91, commitment of RMSEA = 0.032 GFI = 0.97. This means that these dimensions (belief, ritual, social, commitment) can reflect the religiosity variables positively and fit empirical data. The most dominant dimension reflecting religiosity is the social dimension with an average factor loading value >0.05, and the weakest one that reflects religiosity is confidence because many items have a loading factor <0.05.